« Après la césarienne, tu auras toujours des problèmes » : hiérarchisation des modèles de naissance en Inde du Nord - Lucia Gentile (Anthropologie & Santé, 2025)
Since the 2000s, Indian government programmes aimed at institutionalising childbirth have led to a medicalisation of childbirth. Among the various techniques, caesarean section is one of the most contested outcomes. This article examines the impact of this model of childbirth on the representations and practices of Indian women, with a focus on the town of Bhuj, in the State of Gujarat, as a case study. The ethnographic research revealed a hierarchy of childbirth methods, along with various strategies employed to avoid Caesarean sections. These practices stem from local knowledge disseminated by the dāī, the vernacular term for those who accompany women during the perinatal period. The dāī present themselves as the guardians of vaginal childbirth. Thanks to Caesarean sections, the members of this vanishing profession have found the means to restore their own legitimacy in an environment dominated by biomedicine.